IMPLEMENTASI MODEL PEMBELAJARAN BLENDED LEARNING MENGGUNAKAN LMS GOOGLE CLASSROOM MATA PELAJARAN MATEMATIKA MATERI EKSPONEN DAN LOGARITMA PADA SISWA KELAS X ACP SMK NEGERI 1 BANYUANYAR: SMK NEGERI 1 BANYUANYAR PROBOLINGGO DAN SMK NEGERI 1 PUJER BONDOWOSO - DIAH VIALITA DEWI & AGENG JELLY PURWANTO (Dewan Pendidikan Bondowoso, 2021)
The COVID-19 pandemic has become the center of attention of the government and society at this time, so that many policies in various fields get new policies, especially in education. Education is closely related to the formation of a crowd, especially face-to-face learning. So that education policy should really be a concern of the government because it relates to the future of students. One of the government policies is the implementation of Distance Learning (DL). With DL, schools need to innovate to answer these challenges. SMK Negeri 1 Banyuanyar facilitates students in DL by Google Classroom (GC) with the Blended Learning Learning Model. This research is classroom action research using a qualitative approach. From the results of observations obtained data that from 35 students who took part in the mathematical learning of exponential and logarithmic materials there were 15 students who had not yet completed, so that classical student completeness was still 43%. So that the implementation of the Blended Learning Learning Model using the LMS Google Classroom Mathematics subject matter of exponentials and logarithms in 10th grade of ACP students of SMK Negeri 1 Banyuanyar can be carried out smoothly even though there are several obstacles.